Kidney Histology of Wistar Rats (Rattus norvegicus Berkenhout 1769) Due to White Coffee - Agi, Yola Alunsa; Titrawani, Titrawani (Jurnal Biologi Universitas Andalas, 2021)
Coffee is a drink that is very popular with the people of Indonesia and in other countries. Coffee has many benefits but on the other hand, coffee can also damage health, the dangerous content in coffee is caffeine and cafeeic acid. The effect of coffee consumption is still a matter of controversy, one of which is the effect on the kidneys because the kidneys are the main excretory organ for removing metabolic waste from the body. The kidney is the second organ after the liver, which is most often the target of damage by chemicals. This study aims to determine the effect of multilevel doses of white coffee on the histological picture of rats' kidneys. This research is a completely randomized design study with four 4 treatments and four 4 replications. Consists of K (distilled water), P1 (0.36 ml), P2 (1.08 ml) and P3 (2.16 ml). The results of this study showed that macroscopic observations of the administration of white coffee civet coffee solution with different doses showed that the kidneys looked normal. It is characterized by the shape of the kidney like a pea and brownish-red in color. The P0 group was significantly different from the P1, P2, P3 groups. The P1 group was significantly different from the P0 group and the P2 group, P3. The P2 group was significantly different from the P0, P1, and P2 groups. The P3 group was significantly different from the P0, P1, and P2 groups. This study concluded that white coffee in multilevel doses affects the histopathology of kidneys in rats.